Evaluation of the Antimicrobial and Anti-inflammatory Properties of Bacillus-DFM (Norum™) in Broiler Chickens Infected With Salmonella Enteritidis - Adhikari, Bishnu; Hernandez-Patlan, Daniel; Solis-Cruz, Bruno; Kwon, Young Min; Arreguin, Margarita A.; Latorre, Juan D.; Hernandez-Velasco, Xochitl; Hargis, Billy M.; Tellez-Isaias, Guillermo (Frontiers in Veterinary Science, 2019)
Restrictions of in-feed antibiotics use in poultry has pushed researches towards finding their appropriate alternatives such as Direct-Fed Microbials (DFM). In this study, previously tested Bacillus isolates (B. subtilis and B. amyloliquefaciens) were used to evaluate their therapeutic and prophylactic effects against Salmonella Enteritidis in broiler chickens. For this purpose, initial antibacterial activity of Bacillus-DFM (104 spores/g or 106 spores/g) against S. Enteritidis colonization in crop, proventriculus and intestine was investigated using in vitro digestive model. Furthermore, to evaluate therapeutic and prophylactic effects of Bacillus-DFM (104 spores/g) against S. Enteritidis colonization, 25 broiler chickens were randomly allocated to either DFM or Control group (without Bacillus-DFM). Chickens were orally gavaged with 104 cfu of S. Enteritidis per chicken at 1-d old, and ceca-cecal tonsils (CCT) and crop were collected at 3 and 10 days later during therapeutic study, whereas they were orally gavaged with 107 cfu of S. Enteritidis per chicken at 6-d old and CCT and crop were collected 24 h later from two independent trials during prophylactic study. Serum superoxide dismutase (SOD), FITC-d and intestinal IgA levels were reported for both chicken studies, in addition of cecal microbiota analysis from therapeutic study. DFM significantly reduced S. Enteritidis concentration in intestine compartment, and in both proventriculus and intestine compartments as compared to the Control when used at 104 spores/g and 106 spores/g, respectively (p<0.05). DFM significantly reduced FITC-d and IgA, and SOD and IgA levels (p<0.05) as compared to the Control in therapeutic and prophylactic studies, respectively. Interestingly, in the therapeutic study, there was significant difference in bacterial community structure between DFM and Control. Likewise, phylum Actinobacteria and the genera Bifidobacterium, Roseburia, Proteus, and cc_115 were decreased, while the genus Streptococcus was enriched significantly in DFM group as compared to the Control (MetagenomeSeq, p<0.05). Thus, the overall results suggest that the Bacillus-DFM can reduce S. Enteritidis colonization and improve the intestinal health in chickens through mechanism(s) that might involve the modulation of gut microbiota and their metabolic pathways. The prophylacit and therapeutic effects of Bacillus-DFM at higher dose (106 spores/g) in broiler chickens are currently being evalulated.